Nepal: Need for an Alternative Food System - Tripathi, Damodar; Kaini, Tika Raj (Asian Journal of Population Sciences, 2023)
The neo-liberal global food system is facing a huge criticism in recent years. It has some serious problems; two of them are the major ones. First, it could not provide enough and timely supply of food to the people of different regions and sections of the society. Another, it failed to cope with the changing socio-economic drivers of food system; such as migration and climate change. Therefore, searching for an alternative system to ensure food and nutrition security of the global humanity is going under different ways. In this respect, this paper critically evaluates the modern food system in Nepalese context. It utilizes two key perspectives; climate change and Global Value Chain (GVC) and argues that Nepal must find an alternative model of food system to ensure sustainable food supply and food security of the country. The paper primarily relies on secondary sources of data including journal articles, census and survey reports, and news articles.